A Qualitative Review of 18 Years of Research on Workplace Deviance: New Vectors and Future Research Directions. Issue 4 (8th August 2021) - Malik, Akanksha; Sinha, Shuchi; Goel, Sanjay
ABSTRACT: Workplace deviance is a major cause of concern for organizations. It leads to an unpleasant work environment and results in decreased productivity, as well as financial and reputational losses for the organization. This paper synthesizes the vast amount of literature in the field of workplace deviance by qualitatively reviewing 245 papers published from 2003 till October 2020, highlighting the theoretical frameworks and set of antecedents of negative workplace deviant behavior. It further lays out future research directions concordant with the changing nature and scope of acts of deviance in the workplace that are rapidly transforming due to technology advancement, infusion and globalization. We discuss the changing socio-technological factors and their implications for perpetrator-victim dynamics and urge future researchers to study workplace deviance within this context.